Implementation of Fuzzy Logic Control on a Tower Copter - Fahmizal; Yanu Kharisma, Daffa; Pramono, Subuh (Peneliti Teknologi Teknik Indonesia, 2023)
Air transport has become a major attraction for scientists in the last decade, to carry out developments in the fields of firefighting, military, and commercial purposes. A quadcopter is a helicopter with four rotors. There are four arms connected to the main control and each arm has a motor with a rotor. In this study, the position control of a tower control is presented. A Fuzzy Logic Controller (FLC) is proposed, and it performance is compared with PID control. The hardware implementation test shows that FLC is superior to PID. The hardware testing shows that the settling time of the FLC control response is 0.5s while the PID control response is 1.2s. That means FLC settling time is faster by 58.33% compared to PID.